RESPON PERTUMBUHAN TANAMAN SORGUM (SORGHUM BICOLOR (L.) MOENCH) TERHADAP PENGGUNAAN COCOPEAT, PUPUK KANDANG SAPI DAN PUPUK SILIKAT DI LAHAN KERING LOMBOK UTARA - Alkhairi, Muhammad; Suwardji, Suwardji; Aryabakti, Lalu Arifin (Journal of Soil Quality and Management, 2024)
Problems with Entisol soil fertility in the Dry Land of North Lombok Regency, which is dominated by sandy soil. This is a major factor in carrying out agricultural production activities on dry land in the North Lombok region. One of the efforts that must be made to increase soil fertility is by modifying the root area through the addition of soil amendments such as manure and cocopeat. The purpose of this study was to determine the growth response of sorghum plants to the application of cocopeat combined with cow manure in dry land. The method used in this research is an experimental method with field experiments. The experimental design in this study used a randomized block design (RBD) with 5 treatments, P0 (soil/control), P1 (100 kg/ha silicate fertilizer), P2 (10 tonnes/ha manure + 100 kg/ha silicate fertilizer), P3 (10 tons/ha cocopeat + 100 kg/ha silicate fertilizer), P4 (10 tons/ha manure + 10 tons/ha cocopeat + 200 kg/ha silicate fertilizer). Each treatment was repeated 4 times to obtain 20 experimental units. The effect of giving a combination of manure and cocopeat on sorghum plants showed significant results on plant height and plant stem diameter at each observation, namely at plant ages 25, 32, 39 and 46 HST.